P169 Delayed diagnosis of inflammatory bowel disease in women: Characterization and use of health resources. (21st January 2022) - Sempere Robles, L; Bernabeu, P; Cameo Lorenzo, J I; Laveda, R; García, M F; Aguas, M; Belén, O; Zapater, P; van-der Hofstadt, C; Jover, R; Gutiérrez, A; Ruiz, M T
Abstract: Background: Delayed diagnosis of IBD is associated with increased complications. Female gender is one of the factors most frequently associated with delayed diagnosis. Higher prevalence of functional gastrointestinal disorders in women probably hinders the diagnosis of IBD. The aim of this study is to explore delayed diagnosis of IBD and assess differences between women and men in healthcare access routes. Methods: This multicentre prospective cohort study included 190 patients with newly diagnosed IBD. Data were collected on clinical and demographic characteristics, IBD activity and systematic reconstruction of the diagnostic process in a semi-structured interview together with a review of their medical record. Results: Figure 1 shows clinical and demographic characteristics. In CD, patients' symptoms were similar between both genders, except for a higher incidence of bowel incontinence, arthralgias, asthenia and other symptoms in women. In UC, there was no gender difference in clinical presentation. Overall, the median time from symptom onset to IBD diagnosis was 4.5(2.1–12.9) months, being significantly longer in women than in men, 7.8(3.3–18.9) vs. 3.8(1.7–7.8) p<0.001. In diagnostic process, the time from symptom onset to initial physician visit was 0.7(0.26–2) months with no statistically significant differences between women and men. While the time from initial physician visit to IBD diagnosis was 3.4(1.1–7.4) months with a longer time in women than in men 4.2(1.9–11.1) vs 2.2(0.82–5.1) p< 0.001. Figure 2 shows the different diagnostic times by sex in CD and UC. Misdiagnosis were reported in 61.6%, women had a higher percentage of misdiagnosis than men, 77.3% vs 48% (OR 3.6; 95% CI 1.9–6.9). These differences between women and men were maintained in CD 83% vs 55.3 (OR 3.9; 95% CI 1.5–9.9) and in UC 68.6% vs 41.8% (OR 3; 95% CI 1.2–7.4). Misdiagnosis were observed in 66/120 (55%) patients evaluated in Emergency Department, 89/166 (53.6%) in Primary Health Care, 25/122 (20.5%) in Gastroenterology Outpatient Clinics, 4/11(36.5) in another medical specialist, and 14/84 (16.7) in Hospital Admission. Women had a higher percentage of misdiagnosis, in Emergency Department 66.1%/44.3% (OR 2.4; 95% CI 1.1–5.1), Primary Health Care 65.1%/42.2% (OR 2.5; 95% CI 1.3–4.7), Gastroenterology Outpatient Clinics 29.5%/11.5% (OR 3.2; 95% CI 1.2–8.4) and Hospital Admission 25.6%/7.3% (OR 4.3; 95% CI 1.1–16.9). Figure 3 shows the distribution of the most frequently misdiagnosed pathologies prior to IBD diagnosis. Conclusion: Delayed diagnosis of IBD in women affects both CD and CU, due to a longer delay in the diagnostic process since the patient consults for the first time. Gender biases in the misdiagnosis of IBD patients occur at all levels of health care.